Socioeconomic status (SES), food insecurity and the double burden of malnutrition within South African households - Brown, James Craig (Health Economics Unit, 2019)
The co-existence of under- and over-nutrition, termed the double burden of malnutrition (DBM), is associated with a high prevalence of both communicable and non-communicable diseases and is becoming a large public health concern. In general, DBM development is associated with populations undergoing a nutrition transition and urbanisation. DBM can exist at a population, household or individual level. The household form is particularly difficult to target with interventions, because households, and particularly mother-child pairs, are often consuming the same foods. For example, frequent consumption of energy dense and nutrient poor ('junk’) foods can concurrently result in overweight adults, but underweight children. Although, household DBM is linked with poverty and food insecurity and its prevalence is steadfastly increasing it is yet to be investigated in South Africa, despite this country being one of the most inequitable in the world. In addition, South Africa has a high prevalence of obesity (34% of adult females obese), undernutrition (9% of children underweight) and poverty (25% unemployment). with a high prevalence of poverty and food insecurity. Therefore, this study aims to estimate the prevalence, and examine the associated factors of DBM, in South African households. Using the nationally representative data from 2014, South Africa National Income Dynamic Survey wave 4, , the prevalence of household DBM pairs (overweight/obese mother and underweight/stunted child) was estimated. Multivariate logistic regression was applied to examine the relationship between mother-child DBM pairs and (i) socioeconomic status (per capita household income, number of household residents, and mother’s race, education, marital status, household head status), (ii) food security (per capita food expenditure), and (iii) potentially important confounders (mother’s age and urban/rural household). The regression was adjusted for mother’s age as a potential confounder. Mother-child DBM prevalence was 11% in this nationally representative sample of South Africa. Mother’s characteristics of being African (adjusted odds [aOR]: 1.3; 95% confidence intervals [95%CI]: 1.0-1.7) and married (aOR: 1.4, 95%CI: 1.1-1.6) were associated with increased odds of DBM. In contrast mother’s having tertiary education (aOR: 0.7, 95%CI: 0.5-1.0) and greater household per capita income (aOR: 0.9, 95%CI: 0.8-1.0) were protective against DBM. This South African household DBM prevalence is higher than most other developing countries and is associated with mother’s being African, married and having less education; as well as households with less per capita income. This high prevalence warrants urgent attention by policy makers to further investigate this issue in South Africa. Moreover, interventions such as Brazil’s “Green my Favela” should be considered to reduce the cost and increase the supply of nutritious foods to impoverishes households of South Africa.